Age structure and growth of the black-ocellated racerunner (Eremias nigrocellata, Reptilia, Lacertidae) in the loess desert of Tajikistan - Artem A. Kidov; Vladimir O. Erashkin; Roman A. Ivolga; Tatyana E. Kondratova; Andrey A. Ivanov (Acta Biologica Sibirica)
The paper presents the results of age and growth studying of the black-ocellated racerunner (Eremias nigrocellata) by skeletochronology. 23 adult individuals (14 females and 9 males) collected on the border of Shaartuz and Nosiri-Khusrav districts in Khatlon region of Tajikistan were studied. All animals, on the section of tubular bones had a birth (hatching) line appearing shortly after the lizards hatching. Females were 1–7 years old (average 3.64 years), and males 1–5 years old (average 3.11 years). In the group of studied animals, the majority of individuals were 2–4 years old (65.2%). The largest number of females were aged three and four years (21.4% each). The male group was dominated by individuals aged four (33.3%), three and two years (22.2% each). Females and males did not differ in size from each other. The body length of the studied females was 55.25–65.61 mm (average 60.28), and males 58.42–63.32 mm (average 60.11). The calculated maximum body length (SVLmax) of females (61.33 mm) did not differ from the length of males (61.57 mm). The growth coefficient (k) of females (0.99) was higher than males (0.87). The annual survival score (S) in females (0.74) was similar to males (0.70). The life expectancy of individuals who survived one wintering (ESP) was 4.35 years for females and 3.88 years for males.